Effect of Surface Roughness Height on the Aerodynamics Performance of Axial Compressor Cascade Blades - Yousif, Assim H; Hassan, Jafar M; Khudar, Omar A. (Nahrain University College of Engineering Journal, 2015)
The performance of fluid handling mechanical parts such as compressor blades are usually significantly affected by the surface roughness, because they often operate in condition of peak output that is close to this flow condition. The influence of surface height roughness of compressor blades has been investigated experimentally under the effect of cascade stagger angle. The experimental results done by using the direct measuring technique showed that the aerodynamic coefficients of compressor cascade blades influences by presences of surface roughness and stagger angle. The lift coefficient, pitching moment coefficient and cascade blade efficiency were reduced, while the drag coefficient is increased, with the increase of height roughness. The height of roughness does eliminate the operating condition of the cascade blades, which reduce the value of the stall angle.